2010
DOI: 10.1007/s10664-010-9134-8
|View full text |Cite
|
Sign up to set email alerts
|

Refining the systematic literature review process—two participant-observer case studies

Abstract: Systematic literature reviews (SLRs) are a major tool for supporting evidencebased software engineering. Adapting the procedures involved in such a review to meet the needs of software engineering and its literature remains an ongoing process. As part of this process of refinement, we undertook two case studies which aimed 1) to compare the use of targeted manual searches with broad automated searches and 2) to compare different methods of reaching a consensus on quality. For Case 1, we compared a tertiary stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 55 publications
1
88
2
4
Order By: Relevance
“…Hence, manual search would be a valuable complement to the automated search in these cases. This is also another aspect that supports the Kitchenham et al's finding regarding the relationship of the two search methods [7].…”
Section: Strategy (P3)supporting
confidence: 81%
See 1 more Smart Citation
“…Hence, manual search would be a valuable complement to the automated search in these cases. This is also another aspect that supports the Kitchenham et al's finding regarding the relationship of the two search methods [7].…”
Section: Strategy (P3)supporting
confidence: 81%
“…Kitchenham et al reported an participant-observer case study [7] that investigated several factors for the search in SLRs: search breadth, gray literature and performance of manual and automated search. The results support a restricted manual search targeting an appropriate set of venues may help to avoid the omission of good quality papers.…”
Section: Related Workmentioning
confidence: 99%
“…Given the results of Study 3, it appears that the benefits of discussion may be more limited than we had expected. Study 2 and the study by Kitchenham et al [24] both favoured discussion among participants but they did not consider whether the additional costs of discussion would lead to significantly better reliability than simply adding another judge and aggregating scores arithmetically. Kitchenham et al [24] found relatively good results by simply taking the median value of three independent scores without any discussion.…”
Section: Recommendations For Quality Assessments For Systematic Reviewsmentioning
confidence: 99%
“…However, in the related papers we found that, with the exception of Kitchenham [24], and apart from studies of randomised controlled trials, there was little empirical evaluation of the use of criteria to determine the quality of studies that are to be used in meta-analysis or systematic reviews, so any evidence-based recommendations are better than nothing.…”
Section: Recommendations For Quality Assessments For Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation